First comprehensive high resolution study of the 28SiH octad bending bands; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 331 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Nikolaeva N. I. Natalya Ivanovna; Sydow C. Christian; Bauerekker (Bauerekker) Z. Kh. Zigurd Khermann (2025, 2025)
Title screen